Use of arable land and transformation processes in the agrarian sector of Ukrainian economy - Zos-Kior, Mykola (Skhid, 2013)
The article explored the question most rational approaches to the use of arable land cultivated with crops while using modern technologies in crop production, allocation of normalized area under the net and engaged fallows, and further transformation of arable land to some extent in hayfields and pasture, based on advanced experience in this regard.